CONCEPTS, THEORETICAL AND METHODOLOGICAL APPROACHES TO The POLITICAL PROCESSES - Ulugbek Hayitov (Scholar Express Journal, 2022)
The article presents the concept of the political process, its peculiarities, the views of world scholars on political processes from a political point of view, the classical approaches. The current state of political processes is comparatively analyzed on the basis of materials from independent Uzbekistan and neighboring countries.
Keywords: political process; political life; political system; political theory